Nacre-mimic Reinforced Ag@reduced Graphene Oxide-Sodium Alginate Composite Film for Wound Healing. Issue 1 (December 2017) - Yan, Xu; Li, Fei; Hu, Kang-Di; Xue, Jingzhe; Pan, Xiao-Feng; He, Tao; Dong, Liang; Wang, Xiang-Ying; Wu, Ya-Dong; Song, Yong-Hong; Xu, Wei-Ping; Lu, Yang
Abstract With the emerging of drug-resistant bacterial and fungal pathogens, there raise the interest of utilizing versatile antimicrobial biomaterials to treat the acute wound. Herein, we report the spraying mediated assembly of a bio-inspired Ag@reduced graphene-sodium alginate (AGSA) composite film for effective wound healing. The obtained film displayed lamellar microstructures similar to the typical "brick-and-mortar" structure in nacre. In this nacre-mimic structure, there are abundant interfacial interactions between nanosheets and polymeric matrix, leading to remarkable reinforcement. As a result, the tensile strength, toughness and Young's modulus have been improved 2.8, 2.3 and 2.7 times compared with pure sodium alginate film, respectively. In the wound healing study, the AGSA film showed effective antimicrobial activities towardsPseudomonas aeruginosa, Escherichia coli andCandida albicans, demonstrating the ability of protecting wound from pathogenic microbial infections. Furthermore, in vivo experiments on rats suggested the effect of AGSA film in promoting the recovery of wound sites. According to MTT assays, heamolysis evaluation andin vivo toxicity assessment, the composite film could be applied as a bio-compatible materialin vitro andin vivo . Results from this work indicated such AGSA film has promising performance for wound healing and suggested great potential for nacre-mimic biomaterials in tissue engineering applications.